Development of a strategic plan by the Mozambican Association of Obstetricians and Gynaecologists: Direct and indirect effects. (18th July 2014) - Osman, Nafissa B.; Almeida, Maria L.; Ustá, Momade B.; Bique, Cassimo; David, Ernestina
Abstract: The Mozambican Association of Obstetricians and Gynaecologists (AMOG) received support from the FIGO Leadership in Obstetrics and Gynecology for Impact and Change (LOGIC) Initiative in Maternal and Newborn Health (MNH) to strengthen its organizational capacity and to assume leadership in MNH through the development of a strategic plan. The planning process involved identification of key stakeholders; analysis of strengths and weaknesses; stakeholder consultation; consultation with AMOG members; and ratification at the annual general meeting. The participatory process led to the development of vision and mission statements. Furthermore, core values and strategic goals were identified: (1) to contribute to the implementation of governmental plans for improving MNH; (2) to assume leadership in advancing the practice of obstetrics and gynecology through education and training; and (3) to continue to strengthen organizational capacity. Consequently, relationships among members were reinforced and the visibility and recognition of AMOG as a key stakeholder in MNH increased.